1804 Ind. Acts 108 - (:unkn) unknown (My University, 1804)
A Law Entitled a Law Respecting Slaves, § 4: Prohibited a "slave or mulatto" from carrying or possessing a gun, powder, shot, club or other weapon and ammunition.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES